HUBUNGAN PENGETAHUAN DAN PENDIDIKAN IBU DENGAN PEMBERIAN ASI EKSLUSIF DI PUSKESMAS PEMATANG PANGGANG - Manjang, Yunazar; Royani, Ida; Nabil, M (Journal Safety and Healthty, 2024)
Exclusive breastfeeding for 4 months. But now, exclusive breastfeeding for babies is recommended by WHO for 6 months. This study aims to determine the relationship between knowledge and education with exclusive breastfeeding. This type of research uses cross sectional. The population in this study were mothers who breastfeed at Pematang Panggang Health Center totaling 36 respondents with a sampling technique using accidental sampling. The analysis was carried out in two stages, namely Univariate and Bivariate analysis. The statistical test used the chi-square test with a significance level of =5%. The results showed that the study concluded that there was a relationship between knowledge and mother's education simultaneously with exclusive breastfeeding at Pematang Panggang Health Center in 2019 For Pematang Panggang Health Center It is expected to provide more intensive counseling about exclusive breastfeeding so that mothers know about exclusive breastfeeding.